Analisis Supplay Chain Management Terhadap Kesediaan Bahan Pokok - Mursala, Fakri; Tondang, Grace Amalia; Aisyah, Siti (Universitas Labuhanbatu, 2022)
The development of the supply chain management science system makes the application of production arrangements from the producer line to the consumer level. Supply chain management or better known as the supply chain is a system that ensures the proper delivery of management from producers to consumers. In this research, it focuses more on the analysis of the availability of basic ingredients in the community for supply chain management. This study uses a qualitative method by means of a literature review of the existing reading literature and is developed in detail. The supply chain process that ensures the availability of the supply chain is planning, purchasing or procurement, production, warehouse management, order delivery, and order returns, while for the benefits of supply chain management, namely customer satisfaction, increasing revenue, decreasing costs, and increasing asset utilization. , profit increases, and the company gets bigger.